Ansiedade, depressão e qualidade de vida no trabalho em enfermeiros de hospitais públicos de médio e grande porte no município de Aracaju - Sant'Ana, Sílvia Maria da Silva (2016)
The exposure of a nurse to unhealthy and stressful work conditions may lead to depression and compromise the quality of life at work, thus jeopardizing the labor activities and increasing the number of absences because of diseases caused or worsened by work. To evaluate the occurrence of depression and the index of quality of life at work of nurses of four public hospitals in Aracaju. The Hospital Anxiety and Depression Scale (HADS), and the Quality of Life at Work of Nurses (QLWN) were applied in a sample of 221 nurses, as well as a questionnaire, elaborated by the researcher, in order to obtain individual and professional characteristics. The gathering of data happened between November 2014 and April 2015, and afterwards, the descriptive statistics of the variables was done. 44.35% of the nurses showed symptoms of anxiety, and 31.7% symptoms of mild depression. The averages of scores of QLWN were 8.92 for appreciation and institutional recognition, 6.14 for working conditions, safety and remuneration, 11.75 for professional identity and image, and 10.66 for work integration, on a variation of 0 to 20. A negative correlation was noticed between depression and global QLWN, and time of hospital service, tested by the Linear Correlation of Spearman, significant association between depression, pay, and working hours of 36 hours, significant association between QLWN and work shift, between the integration dominion with the team and the number of employments. Conclusion: The results has shown a high occurrence of anxiety and depression when compared with other studies. Quality of life at work is, in general, unsatisfying, especially at work conditions, safety and pay. However, nurses are satisfied with their professional image. The evidence suggests that the presence of symptoms of anxiety and depression lead to a less satisfaction with quality of life at work.